2007
DOI: 10.1103/physrevb.76.174520
|View full text |Cite
|
Sign up to set email alerts
|

Embedded polytypes inBi2Sr2xLaxCuO6

Abstract: We investigate the presence of secondary phases in La-doped Bi-2201 thin films grown by laser ablation. The cation ratios in the target material, the oxygen pressure, and the substrate temperature during the deposition are the main parameters determining the presence of diluted intergrowth and/or polytype aggregates. A statistical model of random intergrowth is used to analyze the x-ray diffraction ͑XRD͒ anomalies caused by hidden defects and to characterize the latter. A detailed structural XRD refinement on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Nevertheless, there are some asymmetries in the profiles of the (0 0 l) family of Sr 2 RuO 4 peaks in figure 1(a), which can be identified more as structural defects rather than secondary phases. These are most likely stacking faults which are known common defects in layered perovskite structures [17,18]. These asymmetries, which were also reported in other studies [19], can be de-convoluted into main peaks and shoulder peaks as shown in figure 3 A similar plot is done for the asymmetric shoulders of the superconducting Sr 2 RuO 4 film in figure 3(c); here no correlation can be observed and so the fitting does not converge as cos 2 θ/sinθ→0.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Nevertheless, there are some asymmetries in the profiles of the (0 0 l) family of Sr 2 RuO 4 peaks in figure 1(a), which can be identified more as structural defects rather than secondary phases. These are most likely stacking faults which are known common defects in layered perovskite structures [17,18]. These asymmetries, which were also reported in other studies [19], can be de-convoluted into main peaks and shoulder peaks as shown in figure 3 A similar plot is done for the asymmetric shoulders of the superconducting Sr 2 RuO 4 film in figure 3(c); here no correlation can be observed and so the fitting does not converge as cos 2 θ/sinθ→0.…”
supporting
confidence: 72%
“…These asymmetries, which were also reported in other studies [19], can be de-convoluted into main peaks and shoulder peaks as shown in figure 3 A similar plot is done for the asymmetric shoulders of the superconducting Sr 2 RuO 4 film in figure 3(c); here no correlation can be observed and so the fitting does not converge as cos 2 θ/sinθ→0. For comparison, a very similar random variation of the c-axis versus cos 2 θ/sinθ is also seen in Bi 2 Sr 2−x La x CuO 6 , as shown in figure 3(c) [17]. An explanation of equation (2) can be found in the supplemental material.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In this section, we present and discuss the results on the Ag–Ge/AlN NMLs, based on X-ray diffraction data and their comparison with the model calculations introduced in the preceding section. For the particular case of annealed sequentially deposited samples under RF bias, to account for the observed nonmonotonous X-ray peak displacements, we used a model for random intercalation that allows the characterization of the guest phase and the estimation of its concentration within the host matrix. Real and simulated TEM pictures are also presented for completion.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As announced in the preceding section, this is incompatible with any kind of strain because in this case the deviations would have the same sign obeying Bragg’s law. The observed anomalous deviations are typical for random intercalation of fixed length polytypes. To find the concentration and nature of the intercalate from the measure of the peak deviations, we used the model introduced in ref in similar circumstances. In momentum space, the momentum transfer along the normal to the family of diffracting planes is .…”
Section: Results and Discussionmentioning
confidence: 99%